Structural and cellular basis of vitamin K antagonism. (12th July 2022) - Liu, Shixuan; Shen, Guomin; Li, Weikai
Abstract: Vitamin K antagonists (VKAs), such as warfarin, are oral anticoagulants widely used to treat and prevent thromboembolic diseases. Therapeutic use of these drugs requires frequent monitoring and dose adjustments, whereas overdose often causes severe bleeding. Addressing these drawbacks requires mechanistic understandings at cellular and structural levels. As the target of VKAs, vitamin K epoxide reductase (VKOR) generates the active, hydroquinone form of vitamin K, which in turn drives the γ‐carboxylation of several coagulation factors required for their activity. Crystal structures revealed that VKAs inhibit VKOR via mimicking its catalytic process. At the active site, two strong hydrogen bonds that facilitate the catalysis also afford the binding specificity for VKAs. Binding of VKAs induces a global change from open to closed conformation. Similar conformational change is induced by substrate binding to promote an electron transfer process that reduces the VKOR active site. In the cellular environment, reducing partner proteins or small reducing molecules may afford electrons to maintain the VKOR activity. The catalysis and VKA inhibition require VKOR in different cellular redox states, explaining the complex kinetics behavior of VKAs. Recent studies also revealed the mechanisms underlying warfarin resistance, warfarin dose variation, and antidoting by vitamin K. These mechanistic understandings may lead to improved anticoagulation strategies targeting the vitamin K cycle.